Implementrasi Pendekatan REBT dalam Konseling Kelompok Untuk Mereduksi Perilaku Self-Harm - Pamungkas, Bintang; M.Sayyid Ramadhan; M.Rizky Ramadhan; Sofyan Abdi; Afra Hasna (ILIN Institute, 2025)
Mental health is an important part of human well-being, both physically and psychologically. Not only the ability to solve problems, but also the ability to deal with stress that arises in oneself. In this modern era, teenagers aged 10-19 years have stress levels reaching 6.2%, which if not handled properly can cause depression and even self-harm or suicidal behavior (Suhartini et al., 2022). The research was conducted at SMKN 50 Jakarta with a qualitative approach. Purposive sampling technique was used for sample selection. The sources were chosen subjectively by the researcher, from four sources, two of whom showed symptoms of self-harm, such as cutting their hands with sharp objects, hitting walls, and slapping their cheeks until they bruised. The research results show that self-harm is triggered by less harmonious family conditions, which encourage unnatural behavior. REBT is the right choice for self-harm. With this approach, it is hoped that students can change the way they think and manage their emotions better.